Android-Based Online Bookstore System Design - Erich Satia Wibawa; Dwi Pujining Tyas; Indah Tritantri (International Journal of Research and Applied Technology (INJURATECH), 2023)
Indonesia is one of the countries with low interest in reading, given the importance of reading to increase human knowledge, by utilizing technological developments, an application is made that provides books in digital form. The purpose of this research is to design an online bookstore system that can be accessed using an android device. This application serves as a platform for readers so that they can increase their interest in reading with various digital books that can be accessed for free or paid. The research that was conducted was by using a descriptive method of analysis with a qualitative approach. This application development process uses an object-oriented approach, namely system development life-cycle prototyping. The result of this research is to produce an online bookstore and an android-based audiobook that can be read and listened to for free or paid. In the application, there are various types of digital books with features that make it easier for readers. With this android-based online bookstore, users can read books anywhere and anytime without having to carry a lot of books. This research was conducted to make it easier for readers who want to read books effectively and efficiently with only one android device. In the end, this application is a reading medium to improve reading habits, especially the Indonesian people.